Fabrication of carbon nanotube reinforced aluminum alloy composites by vacuum-assisted infiltration technique - Kucukyildirim, Bedri Onur; Eker, Aysegul Akdogan (SAGE PUBLICATIONS LTD, 2021)
Carbon nanotube (CNT) reinforced 6063 aluminum (Al) matrix composites were fabricated by vacuum-assisted infiltration of molten 6063 Al alloy into a CNT preform to enhance compressive mechanical properties. Preforms were produced with different amounts of chemically functionalized CNTs to obtain three different CNT reinforcement ratios (0.25, 0.50, and 0.75 wt.%). In addition to the investigation of properties throughout all stages of the preparation of the CNTs, CNT preforms and fabricated composites by various methods of analysis, all steps of the composite fabrication process, as well as the compressive mechanical test results of CNT/6063 Al composites are all discussed. Approximately 250% and 280% increases in the yield and ultimate compressive strength, respectively, are achieved with low-purity CNT addition. Consequently, it is confirmed from the micrographs that the mechanical enhancements of the composites are mainly interrelated with the successful bridging of CNTs in the matrix material. Meanwhile, it is observed that both the modified Halpin-Tsai model and the modified Halpin-Tsai model developed with a dispersion-based prediction model results match with experimental results. Overall results can be accepted as developmental stages of significant progress in the CNT preform reinforced metal matrix composites field.
Keywords: Carbon nanotube; metal matrix composites; preform; infiltration; mechanical properties; MATRIX NANOCOMPOSITES; Materials Science